Analyzing Users’ Perceptions on Solar Electrification: A Study on Villagers in off-grid Regions - Khan, Tahsina; Hassan, Farheen; Hasan, Md. M. (AIUB Journal of Business and Economics, 2019)
This empirical study sought to ascertain the perception of rural communities in Bangladesh about the development opportunities derived from the emergent adoption of solar home system (SHS). Using the semi-structured questionnaire, this study analyzed information gathered from one hundred and seventy one respondents drawn purposively from two villages locally known as Charking and Boalia, situated in the Noakhali and Shirajganj districts respectively. The survey was conducted between October, 2017 and January 2018 including field observations in the selected sites and in-depth interviews to facilitate the data collection process. Questionnaire items, which were primarily adopted from prior studies, measure the responses of the survey participants in a seven point Likert-scale ranging from ‘strongly agree’ to ‘strongly disagree’. Since the study focuses more on exploring users’ perception regarding SHS adoption, basic descriptive statistics of percentage, frequencies, and cross tab were incorporated in the analysis. Results of the study reveal that, household users in the off-grid rural locations benefit from the access to solar electricity through improvement in their living conditions and enhanced social status. In addition to this, the rural families avail convenient in-house lighting, security at night and better educational opportunities for the children. With this backdrop, findings of the study add value to the current literature on impact assessment of solar electrification and provide strategic insights for policymakers to promote the usage of renewable energy technology among the rural populations of the country.